2014
DOI: 10.3389/fnbeh.2014.00296
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study on the cognitive effect of alpha neurofeedback training in patients with major depressive disorder

Abstract: Cognitive deficits are core symptoms of depression. This study aims to investigate whether neurofeedback (NF) training can improve working memory (WM) performance in patients with major depressive disorder (MDD). The NF group (n = 40) underwent eight NF sessions and was compared to a non-interventional control group (n = 20). The NF protocol aimed to increase the individual upper alpha power in the parieto-occipital area of the scalp. Main cognitive variable was WM, which was measured pre- and post- training a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 74 publications
6
67
1
1
Order By: Relevance
“…Generally, successful modulation of EEG band power is associated with cognitive and behavioral improvements (Kropotov 2009; Gruzelier 2014; Kober et al 2015a, b; Hofer et al 2014; Reichert et al 2016). For instance, voluntary up-regulation of the upper alpha frequency band (UA, about 10–12 Hz) generally leads to improvements in working memory (WM) and short-term memory performance (Escolano et al 2011, 2012, 2013, 2014; Angelakis et al 2007; Nan et al 2012). It is assumed that alpha activity inhibits unnecessary or conflicting processes to the task being performed, thus facilitating attention and memory by actively suppressing distracting stimuli (Klimesch et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, successful modulation of EEG band power is associated with cognitive and behavioral improvements (Kropotov 2009; Gruzelier 2014; Kober et al 2015a, b; Hofer et al 2014; Reichert et al 2016). For instance, voluntary up-regulation of the upper alpha frequency band (UA, about 10–12 Hz) generally leads to improvements in working memory (WM) and short-term memory performance (Escolano et al 2011, 2012, 2013, 2014; Angelakis et al 2007; Nan et al 2012). It is assumed that alpha activity inhibits unnecessary or conflicting processes to the task being performed, thus facilitating attention and memory by actively suppressing distracting stimuli (Klimesch et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We used an UA based NF training, since the two chronic stroke patients showed deficits in memory functions prior to the NF training. Based on the literature, UA based NF training should have specific positive effects on memory functions (Escolano et al 2011, 2012, 2013, 2014; Angelakis et al 2007; Nan et al 2012). We compared the results of the two stroke patients to the results of a healthy, elderly control group.…”
Section: Introductionmentioning
confidence: 99%
“…One possible goal is enhancement of neurocognitive performances. A first study comparing the cognitive performances of a neurofeedback training group to a non-interventional control group in a sample of MDD patients (n = 60) showed significant improvement in working memory and processing speed with medium to large effect sizes [95]. However, there are some limitations that need to be considered, like the lacking of randomization and mixed depressive states of patients.…”
Section: Neuromodulation Techniques: Neurostimulation and Neurofeedbamentioning
confidence: 99%
“…Power in 8-12 Hz band increased predominantly over central areas of the cortex, indicating that patients modulated sensory-motor mu rhythm rather than a wide-spread alpha rhythm. Recently there have been several controlled randomised studies involving patients which demonstrated that people can successfully learn to increase power in the upper alpha (10-12 Hz) frequency band, resulting in improved memory performance (Escolano et al 2014, Kober et al 2015. A person can also be trained to decrease SMR using NF.…”
mentioning
confidence: 99%